Implementasi Manajemen Strategik dalam Meningkatkan Mutu Pendidikan di SMK YP79 Majalaya Kabupaten Bandung - Silviani, Alien; Marisan, Susan; Yoseptry, Ricky; Noer, Nia Zulfa Septia; Ratnawulan, Teti (STKIP PGRI SITUBONDO, 2024)
This research is motivated by educational problems faced by the Indonesian nation, namely the low quality of educational education at every level and educational unit. An education unit can be said to be of quality if it can deliver students in developing abilities and shaping the character and civilization of a dignified nation in order to educate the nation's life in accordance with the objectives of national education as stated in Law No. 20 of 2003 concerning the national education system (Sisdiknas) article 3. Strategic management is an important thing to do to improve the quality of education by analyzing internal and external factors through SWOT analysis. The purpose of this study is to obtain an overview of the Implementation of Strategic Management in Improving the Quality of Education. This research uses a qualitative approach with Descriptive Analytical method at SMK YP79 Majalaya, Bandung Regency. Strategic Implementation at SMK YP79 Majalaya implements Edward Deming's management function, namely the PDCA cycle (Plan, Do, Check. Act). The results of the study are: 1) SMK YP79 Majalaya applies strategic management according to the National Education Standard (SNP) in accordance with the characteristics of effective and quality-oriented schools, 2) In designing strategic education at SMK YP79 Majalaya is carried out by identifying the internal and external environment of the school using the SWOT analysis method, 3) SMK YP79 Majalaya involves all stakeholders both the role of the principal, teachers, and committees.